PENGARUH HARGA DIRI TERHADAP KECERDASAN MORAL PADA SISWA SMP DI KARAWANG - Citra Cartika; Wina Lova Riza; Devi Marganing Tyas (Empowerment Jurnal Mahasiswa Psikologi Universitas Buana Perjuangan Karawang, 2025)
Moral intelligence is the ability that helps adolescents distinguish right from wrong and act according to moral values ​​amidst the rampant moral degradation. This study aims to determine the effect of self-esteem on moral intelligence in junior high school students in Karawang. The method used is a quantitative approach with a causal design. The sample of 205 junior high school students in Karawang was obtained using the Cohen formula with an effect size of 0.1 and an error rate (α) of 1%, through an incidental sampling technique. The research instrument was a self-esteem scale constructed based on the theory of Heatherton and Polivy, and a moral intelligence scale using the Moral Competency Inventory (MCI) from Lennick and Kiel. Data analysis shows that self-esteem has a significant value of 0.000 <0.05, so Ha is accepted and H0 is rejected. This means that there is an effect of self-esteem on the moral intelligence of junior high school students in Karawang. The results of the determination test showed an R square value of 0.193, so that self-esteem has a 19.3% effect on moral intelligence, while the remaining 80.7% is influenced by other factors not examined. Kecerdasan moral adalah kemampuan yang membantu remaja membedakan benar dan salah serta bertindak sesuai nilai moral di tengah maraknya degradasi moral. Penelitian ini bertujuan mengetahui pengaruh harga diri terhadap kecerdasan moral pada siswa SMP di Karawang. Metode yang digunakan adalah pendekatan kuantitatif dengan desain kausal. Sampel berjumlah 205 siswa SMP di Karawang yang diperoleh menggunakan rumus Cohen dengan effect size 0,1 dan tingkat kesalahan (α) 1%, melalui teknik incidental sampling. Instrumen penelitian berupa skala harga diri yang dikonstruksikan berdasarkan teori Heatherton dan Polivy, serta skala kecerdasan moral menggunakan Moral Competency Inventory (MCI) dari Lennick dan Kiel. Analisis data menunjukkan harga diri memiliki nilai signifikan 0,000 < 0,05, sehingga Ha diterima dan H0 ditolak. Hal ini berarti terdapat pengaruh harga diri terhadap kecerdasan moral siswa SMP di Karawang. Hasil uji determinasi menunjukkan nilai R square sebesar 0,193, sehingga harga diri berpengaruh 19,3% terhadap kecerdasan moral, sedangkan 80,7% sisanya dipengaruhi faktor lain yang tidak diteliti.